1976
DOI: 10.1111/j.1365-2125.1976.tb00604.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of smoking on the intersubject variation in pentazocine elimination.

Abstract: The cumulative urinary excretion over 24 h of pentazocine, under conditions of acidic urinary pH, has been measured in smokers and non‐ smokers using both male and female subjects (seventy subjects in total). A restricted urban population was studied. An overall three‐ fold inter‐subject variation in elimination was observed. The cumulative urinary excretion of pentazocine was normally distributed in both smokers and non‐smokers. Smokers metabolize 40% more pentazocine than non‐smokers. It is concluded that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In all subjects studied, cessation of smoking produced a prolongation of caffeine and antipyrine half-lives and a decrease in caffeine and antipyrine clearance, although the magnitude ofchange was not predictable for any individual subject. This is consistent with earlier reports showing enhancement of hepatic drug metabolism by cigarette smoking (Hart et al 1976;Vaughan et al 1976;Parsons & Neims 1978;Grygiel & Birkett 198 1;Grech-Belanger et al 1985). Parsons and Neims (1978) reported a 50% reduction in caffeine half-life and increased caffeine clearance in 13 healthy smokers compared with a separate control group of non-smokers.…”
Section: Discussionsupporting
confidence: 94%
“…In all subjects studied, cessation of smoking produced a prolongation of caffeine and antipyrine half-lives and a decrease in caffeine and antipyrine clearance, although the magnitude ofchange was not predictable for any individual subject. This is consistent with earlier reports showing enhancement of hepatic drug metabolism by cigarette smoking (Hart et al 1976;Vaughan et al 1976;Parsons & Neims 1978;Grygiel & Birkett 198 1;Grech-Belanger et al 1985). Parsons and Neims (1978) reported a 50% reduction in caffeine half-life and increased caffeine clearance in 13 healthy smokers compared with a separate control group of non-smokers.…”
Section: Discussionsupporting
confidence: 94%
“…64,65 Keeri-Szanto and Pomeroy demonstrated 66 in his study that smokers required higher doses of pentazocine to attain the same analgesic effect compared with lifelong nonsmokers. Vaughan et al 67 showed that smoking increases metabolic clearance of pentazocine, and hence their urine levels of the metabolites were reduced by 40%. The effect of smoking on codeine was studied by Yue et al 68 and concluded that smoking induced the glucuronidation of codeine.…”
Section: Discussionmentioning
confidence: 99%
“…Here, recent evidence indicates that people differ in their ability to metabolize opioids [52,53]. Smokers probably because of enzyme induction by nicotine have been reported to have less pain efficacy from propoxyphene [54], demonstrate increased metabolic clearance of pentazocine [55], require high doses of pentazocine [56], and have significantly lower levels of hydrocodone [31] vs nonsmokers. Thus, the requirement for more opioids in smokers and actual demonstration of ADTBs (the fourth line of evidence) could be a result of differences in the metabolism of opioids between smokers and nonsmokers [20].…”
Section: Discussionmentioning
confidence: 99%